Analisis Kebijakan Pendidikan Islam di Malaysia - Abdul Basyid Has (STAIN Bengkalis, 2022)
Malaysia is a country that has many ethnic groups with a total population of around 28 million people. With the dominance of the Malay tribe, parts of China and India made the government system of the Malaysian state apply the royal system. The leader of the country is led by the king or what is called Pertuan Agung. The domination of Malays and adherents of Islam in Malaysia has had an impact on the educational policies taken by the state. The Malaysian state Education Act 1996 contains the teachings of Islam and morals in the education system in Malaysia. However, actually the educational model and the background to the emergence of the education system in Malaysia which regulates the application of Islam and morals still need to be studied more deeply. So, researchers are interested in this. The research method used is library research (literature study), used analysis is comparative analysis. The results of the study show that the educational model is carried out thoroughly by the Malaysian ministry of education. The background that arises is the result of the desire to make the educational outcomes of students become someone who is balanced and harmonious between intellectual, spiritual, emotional and physical based on belief in and obedience to God.